1-(2-Hydroxy-5-methoxyphenyl)ethan-1-one N-[(E)-1-(2-hydroxy-5-methoxyphenyl)ethylidene]hydrazone - Zhang, Jin-Hua (International Union of Crystallography, 2007)
In the title molecule, C(18)H(20)N(2)O(4), which resides on a crystallographic centre of inversion (at the centre of the N—N bond), all non-H atoms apart from the methoxy substituent are approximately coplanar. The structure displays intramolecular O—H⋯N hydrogen bonding.